Analisis Determinasi Tingkat Kemiskinan Dengan Zakat sebagai Variabel Moderating - Nurul, Azizah; Rahman, Taufikur (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
This study aims to determine the effect of Non-Cash Food Assistance (BPNT) and Family Hope Program (PKH) on poverty levels with zakat as a moderating variable. This research method uses quantitative methods with secondary data obtained from Lazis-NU, Social Service and BPS. The data used is the 2019-2022 time series data in Susukan District. The population in this study is Susukan District, Semarang Regency with a saturated sampling technique and changing annual data to monthly (data interpolation). In testing the hypothesis of this study using Moderate Regression Analysis (MRA) is a special application of linear regression where the regression equation includes factors that interact with each other. This research was assisted by the eviews 10 application in data processing. The results showed that Non-Cash Food Assistance (BPNT) had a negative and significant effect on poverty, while the Family Hope Program (PKH) had a positive and significant effect on poverty. Then the Non-Cash Food Assistance (BPNT) and the Family Hope Program (PKH) were able to moderate the effect of the Non-Cash Food Assistance (BPNT) and the Family Hope Program (PKH) on poverty.